2006
DOI: 10.1063/1.2194541
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and conformation of tetrapyridyl-porphyrin molecules on Ag(111)

Abstract: We present a low-temperature scanning tunneling microscopy (STM) study on the supramolecular ordering of tetrapyridyl-porphyrin (TPyP) molecules on Ag(111). Vapor deposition in a wide substrate temperature range reveals that TPyP molecules easily diffuse and self-assemble into large, highly ordered chiral domains. We identify two mirror-symmetric unit cells, each containing two differently oriented molecules. From an analysis of the respective arrangement it is concluded that lateral intermolecular interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
206
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(231 citation statements)
references
References 55 publications
22
206
1
Order By: Relevance
“…Therefore, our model suggests that one driving force for the different organic architectures is the interplay between intermolecular interactions and the epitaxial fit to the Ag atomic lattice. 8,18 In the STM images (cf. Figure 2a,c), the observed highly regular pattern of different brightness supports our model and thus the arguments of the commensurate networks.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our model suggests that one driving force for the different organic architectures is the interplay between intermolecular interactions and the epitaxial fit to the Ag atomic lattice. 8,18 In the STM images (cf. Figure 2a,c), the observed highly regular pattern of different brightness supports our model and thus the arguments of the commensurate networks.…”
Section: Resultsmentioning
confidence: 99%
“…1 Recently, it was shown that the Cu(111) surface can produce almost perfect layers of graphene by the dehydrogenation of hydrocarbon precursor molecules. 2,3 Scanning tunneling microscopy 4 (STM) is a powerful tool to study the adsorption geometry of different molecules on a conducting surface, 5,6 diffusion processes of single molecules 7 or atoms 8 and even to manipulate single molecules with the STM tip. 9,10 Porphyrins and phthalocyanines are the most studied organic molecules in the monolayer and submonolayer regime.…”
Section: Introductionmentioning
confidence: 99%
“…The observed structures do not show a Moiré pattern for all tunneling conditions we tested; therefore, commensurate models have been constructed. For comparison, the noncommensurate supercell of tetrapyridyl-porphyrin on Ag(111) resulted in an evident modulation of the apparent height of the molecules independent of bias voltage, 50 whereas the apparent height of our molecules is identical for adjacent unit cells.…”
mentioning
confidence: 99%